2016
DOI: 10.1186/s12957-016-0985-3
|View full text |Cite
|
Sign up to set email alerts
|

The expression of microRNA 574-3p as a predictor of postoperative outcome in patients with esophageal squamous cell carcinoma

Abstract: BackgroundDespite advances in radical esophagectomies and adjuvant therapy, the postoperative prognosis in esophageal squamous cell carcinoma (ESCC) patients remains poor. The aim of this study was to identify a molecular signature to predict postoperative favorable outcomes in patients with ESCC.MethodsAs a training data set, total RNA was extracted from formalin-fixed paraffin-embedded samples of surgically removed specimens from 19 ESCC patients who underwent curative esophagectomy. The expression of microR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…In the prostate, the loss of expression of hsa-miR-886-3p was associated with early biochemical relapse (<1 year after radical prostatectomy) [20], but a recent study shows an increased abundance of circulating hsa-miR-886-3p in high-grade compared to low-grade prostate cancer in plasma samples [32]. Notwithstanding, few reports showed an oncogenic action of hsa-miR-886-3p in renal cell carcinoma [33], colorectal carcinoma [34] and esophageal squamous cell carcinoma [35]. A recent finding proposing a nc886/PKR loss mediated doxorubicin cytotoxicity raised a novel view about its specific contribution to chemotherapy response [36].…”
mentioning
confidence: 99%
“…In the prostate, the loss of expression of hsa-miR-886-3p was associated with early biochemical relapse (<1 year after radical prostatectomy) [20], but a recent study shows an increased abundance of circulating hsa-miR-886-3p in high-grade compared to low-grade prostate cancer in plasma samples [32]. Notwithstanding, few reports showed an oncogenic action of hsa-miR-886-3p in renal cell carcinoma [33], colorectal carcinoma [34] and esophageal squamous cell carcinoma [35]. A recent finding proposing a nc886/PKR loss mediated doxorubicin cytotoxicity raised a novel view about its specific contribution to chemotherapy response [36].…”
mentioning
confidence: 99%
“…These data imply that miR-574-3p may exert a tumor suppressor role in K562 cells via regulating IL6/JAK/STAT3 pathway. In previous studies, miR-574-3p has a tumor-promoting role in human osteosarcoma (18), while exerts a tumor suppressor effect in esophageal squamous cell carcinoma (19), indicating that miR-574-3p may play a dual role in regulating cancer progression. Furthermore, it is reported that aberrantly expression of miR-574-3p may play functional roles in regulating the proliferation and metatasis of gastric cancer (16).…”
Section: Discussionmentioning
confidence: 91%
“…The forest plots, Begg’s funnel plots, and sensitivity analyses are shown in Supplementary Figures 1 – 8 according to the logic sequencing of miRNA names. For the included 96 studies, 52 were excluded because the frequency of them evaluating prognostic value of miRNA was equal to 1 3 , 4 , 16 , 18 23 , 26 , 30 , 31 , 39 46 , 48 , 53 , 54 , 56 , 60 , 61 , 64 74 , 77 86 , 92 96 . In addition, although one article reported OS results about miR-193a-5p, it was excluded because it had non-dichotomous miRNA expression value 105 .…”
Section: Resultsmentioning
confidence: 99%